2022
DOI: 10.14245/ns.2244326.163
|View full text |Cite
|
Sign up to set email alerts
|

Risk Analysis Index and Its Recalibrated Version Predict Postoperative Outcomes Better Than 5-Factor Modified Frailty Index in Traumatic Spinal Injury

Abstract: Objective: To assess the discriminative ability of the Risk Analysis Index-administrative (RAI-A) and its recalibrated version (RAI-Rev), compared to the 5-factor modified frailty index (mFI-5), in predicting postoperative outcomes in patients undergoing surgical intervention for traumatic spine injuries (TSIs).Methods: The Current Procedural Terminology (CPT) and International Classification of Disease-9 (ICD-9) and ICD-10 codes were used to identify patients ≥ 18 years who underwent surgical intervention for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 41 publications
2
14
0
Order By: Relevance
“…In concordance with findings in the surgical literature for a range of neurosurgical outcomes, we expected that RAI would have a greater discriminative threshold in these patients, and therefore compared it to mFI‐5 20,22,45 . The RAI utilizes a multifactorial approach by incorporating domains such as comorbidities, functional status, cognition, and nutritional status 45 . While the mFI‐5 takes into account comorbidities and functional status using a binary scale, it does not take into account other crucial aspects of frailty.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…In concordance with findings in the surgical literature for a range of neurosurgical outcomes, we expected that RAI would have a greater discriminative threshold in these patients, and therefore compared it to mFI‐5 20,22,45 . The RAI utilizes a multifactorial approach by incorporating domains such as comorbidities, functional status, cognition, and nutritional status 45 . While the mFI‐5 takes into account comorbidities and functional status using a binary scale, it does not take into account other crucial aspects of frailty.…”
Section: Discussionsupporting
confidence: 65%
“…A preponderance of neurosurgical research has employed the mFI‐5 and mFI‐11 23,44,45 . In concordance with findings in the surgical literature for a range of neurosurgical outcomes, we expected that RAI would have a greater discriminative threshold in these patients, and therefore compared it to mFI‐5 20,22,45 .…”
Section: Discussionsupporting
confidence: 64%
“…To calculate mFI-5, the following comorbidities were considered: hypertension requiring medication, chronic obstructive pulmonary disease, congestive heart failure, diabetes mellitus, and totally or partially dependent functional health status ( Table 1 ). Consistent with previous literature, 15 , 16 , 17 the mFI-5 score was calculated by dividing the sum of all positive variables by the total number of input variables in the database, with a higher mFI-5 score indicating a higher degree of frailty. This research was approved by the Ethics Committee of Hannover Medical.…”
Section: Methodsmentioning
confidence: 98%
“…RAI has proven to be a better predictor of outcomes after surgery and could be a more useful tool during prehabilitation measures. 16…”
mentioning
confidence: 99%
“…RAI has proven to be a better predictor of outcomes after surgery and could be a more useful tool during prehabilitation measures. 16 A recent study by our group has shown RAI's robust predictive ability for brain tumor resection outcomes including IMR, 6 thus raising the possibility of using RAI-based prehabilitaion for IMR patients. Emphasizing on preoperative rehabilitation measures for IMR could improve a patient's physiological reserve and reduce postoperative adverse events.…”
mentioning
confidence: 99%